2022
DOI: 10.1016/j.nantod.2022.101393
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine-assembled nanostimulator enhances dimeric RBD antigen-elicited cross-neutralization against SARS-CoV-2 strains

Abstract: There is an urgent need to develop new vaccination strategies to elevate the cross-neutralization against different SARS-CoV-2 strains. In this study, we construct the spherical amantadine-assembled nanostimulator (AAS). Amantadine as immunostimulating molecules are displayed on the outermost layer of AAS. Molecular mechanism analysis reveals that AAS can activate RIG-I-like receptor (RLR) signaling pathway to increase the expression of type I interferons in vivo . AAS-mediated activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Intending to verify if the novel compounds were cytotoxic to the cells, the cell viability and antiviral activity were evaluated at different concentrations of these compounds in Vero CCL-81 and CALU-3 cell cultures, which demonstrated that AMA derivatives have low cytotoxicity, similarly to AMA in a variety of cell types ( Fink et al., 2021 ; Zhang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intending to verify if the novel compounds were cytotoxic to the cells, the cell viability and antiviral activity were evaluated at different concentrations of these compounds in Vero CCL-81 and CALU-3 cell cultures, which demonstrated that AMA derivatives have low cytotoxicity, similarly to AMA in a variety of cell types ( Fink et al., 2021 ; Zhang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, designing and developing an efficient delivery system for this multipurpose drug can increase its therapeutic effectiveness and reduce its side effects. Some studies have been conducted in this regard [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%